The Effect of Anatomical Torso Media in Problem-Based Learning on Students' Responsibility Attitudes and Cognitive Learning Outcomes in the Digestive System Topic - Ayu Liani; Sri Nopita Primawati; ida royani (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
This study aimed to analyze the effect of using anatomical torso media in Problem-Based Learning (PBL) on students' responsibility attitudes and cognitive learning outcomes in the digestive system topic. The study employed a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The participants were 50 Grade XI students of SMAN 3 Selong, East Lombok, in the 2024/2025 academic year, consisting of 25 students in the experimental class and 25 students in the control class. The experimental class received PBL assisted by anatomical torso media, whereas the control class received PBL without torso media. The research instruments consisted of a four-point Likert-scale questionnaire on responsibility attitudes and cognitive learning tests in the form of multiple-choice and essay items. Responsibility attitude data were analyzed descriptively based on categories, while cognitive learning outcomes were analyzed using normality testing, homogeneity testing, and an independent-samples t-test with SPSS. The results showed a descriptive improvement in responsibility attitudes in the experimental class, with 13 students in the very high category, 11 students in the high category, and 1 student in the moderate category after the treatment. In the control class, no student reached the very high category. The independent-samples t-test showed a significant difference in cognitive learning outcomes between the experimental and control classes, t(48) = 3.128, p = 0.003, with a medium-to-large effect size (d = 0.885). Therefore, the use of anatomical torso media in PBL had a significant effect on students' cognitive learning outcomes and descriptively supported the improvement of responsibility attitudes.